2016
DOI: 10.21037/acs.2016.05.02
|View full text |Cite
|
Sign up to set email alerts
|

Total aortic repair: the new paradigm in the treatment of acute type A aortic dissection

Abstract: The surgical management of acute type A aortic dissection (ATAAD) is in a period of rapid evolution.Understanding the complex physiology and anatomy of both acute and chronic dissection has been enhanced by the ready availability of state of the art imaging techniques. Technical advances in the intraoperative monitoring of organ perfusion, together with adjuncts to limit organ injury and increasing sophistication in open and endovascular surgery have led to a major reduction in both perioperative morbidity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This evolution to endothelialized stent and stable intimal wall opens up the option for specific closure of residual entries and FL by endovascular devices in the chronic phase of the disease with probably lesser risk for endoleak or intimal rupture. 22,23 In addition, the endothelialization process may be supportive for the STABILISE concept, 24,25 in which the entire aortic lumen is stabilized by uncovered stents after rupture of the dissection's septum by balloon and depressurization of the FL. In this case, the endothelialization process could be an important step toward complete healing of the entire aorta.…”
Section: Discussionmentioning
confidence: 99%
“…This evolution to endothelialized stent and stable intimal wall opens up the option for specific closure of residual entries and FL by endovascular devices in the chronic phase of the disease with probably lesser risk for endoleak or intimal rupture. 22,23 In addition, the endothelialization process may be supportive for the STABILISE concept, 24,25 in which the entire aortic lumen is stabilized by uncovered stents after rupture of the dissection's septum by balloon and depressurization of the FL. In this case, the endothelialization process could be an important step toward complete healing of the entire aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, there is no consensus regarding whether to perform limited repair (eg, ascending aortic and hemiarch replacement), followed by late reoperation if needed, or extensive repair (eg, total arch replacement with conventional or frozen elephant trunk) for the index (first) operation. Arguments in favor of limited index repair primarily include lower surgical risk compared with extensive repair—the “live to fight another day” philosophy . In addition, some studies have suggested that limited repair has late outcomes similar to extensive repair, including the development of late aortic dilatation, need for reoperation, and overall survival .…”
Section: Introductionmentioning
confidence: 99%
“…Arguments in favor of limited index repair primarily include lower surgical risk compared with extensive repair 1 -the "live to fight another day" philosophy. 2 In addition, some studies have suggested that limited repair has late outcomes similar to extensive repair, including the development of late aortic dilatation, need for reoperation, and overall survival. [3][4][5] Arguments in favor of extensive index repair focus primarily on the potentially decreased need for late aortic reoperation, operations that are frequently viewed as complex and with much higher risks.…”
mentioning
confidence: 99%
“…Proponents of a pathology-directed expansion of the "tear oriented" approach described by Westaby et al (58) include circumferential arch or arch vessel dissection, arch aneurysm, and descending dissection with true lumen compromise as indications for TAR (53,57,59). Others argue that as outcomes of TAR performed at large volume institutions have improved and are similar to hemiarch outcomes (60), TAR should also be considered for the prevention of mid-or late-term aortic degeneration requiring reoperation (54,61). Matalanis et al propose more extensive arch repair in all ATAD patients using a standardized and simplified TAR technique that has yielded excellent early results (61,62).…”
Section: Arch Extent and Proximal Repairmentioning
confidence: 99%
“…Others argue that as outcomes of TAR performed at large volume institutions have improved and are similar to hemiarch outcomes (60), TAR should also be considered for the prevention of mid-or late-term aortic degeneration requiring reoperation (54,61). Matalanis et al propose more extensive arch repair in all ATAD patients using a standardized and simplified TAR technique that has yielded excellent early results (61,62). Critics caution that outcomes from expert centers cannot be extrapolated to low-volume surgeons burdened with treating ATAD and therefore, TAR cannot reasonably become the standard of care (55,56,(63)(64)(65).…”
Section: Arch Extent and Proximal Repairmentioning
confidence: 99%